Developing the English Teaching Materials to Improve the Students’ Speaking Skills (Case Study at Private MTs Jepara) - Selsa Filia Devi; Shilvyna Rahma; Linda Eka Riyanti; Haryanto Haryanto (Universitas Islam Sultan Agung, 2021)
This study aims to produce a product in the form of English learning textbooks to improve skills speaking, describe the design and implementation of English teaching materials that have been developed to improve speaking skills, describe the effectiveness of developing English teaching materials to improve speaking skills. This research includes the type of research and development (R&D) with stages, namely theoretical and practical studies, field studies, analysis of student and teacher needs, preparation of prototypes, expert tests, prototype revisions, limited trials, evaluations, and revisions of learning models. The population and sample of the study consisted of 40 students of class VIII MTs Walisongo Jepara. Collecting data using the method of observation, interviews, and literature study. This research focuses on the process of learning English for class VIII with the development of teaching materials as media used in English lessons. This research uses the qualitative data analysis method with data reduction, data presentation, conclusion or verification. The results of the study indicate that the design of developing English teaching materials to improve speaking skills is based on the principles of developing teaching materials which include accuracy of coverage and accuracy of content, completeness of components, presentation of language, and appropriate illustrations. The implementation of teaching materials was carried out 4 times in a limited trial. The development of English teaching materials to improve speaking skills was declared effective with an increase in students’ speaking skills in the psychomotor aspect with a mean pretest score of 73, and post-test 91, with an increase in N-Gain of 0.66 in the medium category.